Profil Terapi Antihipertensi dan Antihiperlipidemia Terhadap Fungsi Ginjal Pasien Diabetes Melitus Tipe 2 dengan Komplikasi Penyakit Ginjal Kronis di RSUP Dr. Hasan Sadikin - Rachmaini, Fitri; Amalia, Lia; Rahayu, Cherry (Pharmaceutical Sciences and Research, 2020)
Chronic Kidney Disease (CKD) complication increases the risk of morbidity and mortality in type 2 diabetes mellitus (DMT2) patients. The presence of hypertension and dyslipidemia as comorbidity increases the risk of macrovascular and microvascular complications and further adding to the list of drugs used. Management of this comorbidity is essential to prevent cardiovascular events and minimize kidney damage. This study aimed to evaluate therapeutic profile of antihypertensive and antihyperlipidemia drugs towards kidney function in DMT2 patients with CKD complication at Dr. Hasan Sadikin Hospital. Study was done by using a prospective single cohort design with consecutive sampling technique and obtained 37 patients. Serum creatinine, ureum and eGFR values were collected from December 2017 to February 2018 and became the basis of analysis in this study. The result of this study showed that there was a significant decrease in creatinine serum (p < 0.05), ureum (p < 0.05) and a significant increase in eGFR value (p < 0.05) after three months therapy. Based on the result it can be concluded that therapeutic profile of antihypertensive and antihyperlipidemia can control kidney function in DMT2 patients with CKD complication after three months study based on serum creatinine, ureum and eGFR values.